Representasi Komunikasi Gender dalam Film Penyalin Cahaya - Afra Cholisul Anggraini; Rini Rinawati (UNISBA Press, 2023)
Abstract. This research is entitled Presentation of Communication in Photocopier movie. Photocopier is a movie that discusses sexual violence experienced by a female student named Suryani or Sur. The purpose of this study is to find out how the representation of gender communication is shown in Photocopier movie, also knowing the meaning of denotation, connotation, and myths from gender communication in the film Copying Light itself. In this study, researchers wanted to know the representation of gender communication contained in Photocopier movie. This study used qualitative research methods. This research was conducted based on Semiotic Analysis by Roland Barthes. Roland Barthes himself has three categories of analysis namely denotative meaning, connotative meaning and myth. The object of this research is Film Copying Light, with the research subject Suryani and Tariq. Data collection techniques used in this research are observation, documentation, and literature study. The results of this study are gender communication in the film Photocopier which is analyzed based on three categories from Roland Barthes, namely denotation, connotation and myth. Abstrak. Penelitian ini berjudul Peresentasi Komunikasi dalam Film Penyalin Cahaya. Penyalin Cahaya merupakan film yang membahas kekerasan seksual yang dialami seorang mahasiswi bernama Suryani atau Sur. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana representasi komunikasi gender yang ditampilkan dalam film Penyalin Cahaya, serta mengetahui makna denotasi, konotasi, dan mitos dari komunikasi gender dalam film Penyalin Cahaya sendiri. Dalam penelitian ini peneliti ingin mengetahui representasi komunikasi gender yang terdapat dalam film Penyalin Cahaya. Penelitian ini menggunakan metode penelitian kualitatif, Adapun penelitian ini dilakukan berdasarkan Analisis Semiotika oleh Roland Barthes. Roland Barthes sendiri memiliki tiga kategori analisis yaitu makna denotasi, makna konotasi dan mitos. Objek dari penelitian ini adalah Film Penyalin Cahaya, dengan subjek penelitian Suryani dan Thariq. Teknik pengumpulan data yang digunakan adalah observasi, dokumentasi, dan studi pustaka. Hasil dari penelitian ini adalah komunikasi gender dalam film Penyalin Cahaya yang dianalisis berdasarkan tiga kategori dari Roland Barthes yaitu denotasi, konotasi dan mitos.